In the public interest (Santa Fe, NM Museum of Fine Arts, 1977)
Exhibitions of New Mexico Art, December 18, 1977 - February 26, 1978. listing for the Arthur Johnson Memorial Library Art is found on page 6 of listing of works in the exhibition.
9 paged Leaflet plus a 10 page listing of works in the exhibition
Master list item #: 1
File location is in the Raton File Cabinet drawer 3
Keywords: Library Exhibitions; Museum exhibition; Library Art; Museum Art; Raton, New Mexico